Revitalisasi Pengemasan Produk UMKM “Woro Production” sebagai Upaya Peningkatan Daya Saing Melalui Penerapan Teknologi Inovatif - Mazdadi, Muhammad Itqan; Sari, Anna Khumaira; Normaidah, Normaidah; Saputra, Adryan Maulana; Rahmah, Indah Noor; Ramadhani, Muhammad Irfan; Rahmawati, Nanda Hesti (Jurnal Pengabdian UNDIKMA, 2025)
This community service program aims to strengthen the capacity and technical skills of the “Woro Production” MSME by providing modern packaging equipment and training on its use to improve product efficiency and competitiveness. The implementation method involved training sessions and packaging simulations. Evaluation instruments included observation sheets and interviews to assess the partner’s skills in operating the packaging machine, and the resulting data were analyzed descriptively. The outcomes of this program indicate that participants were able to operate the equipment effectively, and the packaged products demonstrated improved hygiene, practicality, and visual appeal. This initiative is expected to enhance the competitiveness of Woro Production in local, national, and global markets.